2006
DOI: 10.1017/s0967199406003807
|View full text |Cite
|
Sign up to set email alerts
|

ATP content and maturational/developmental ability of bovine oocytes with various cytoplasmic morphologies

Abstract: SummaryWe examined the relationship among morphological appearance (six groups) of bovine oocytes, ATP content and maturational/developmental ability. Oocytes with a brown ooplasm (with or without a dark region) had intermediate levels of ATP at the germinal vesicle (GV) stage and showed higher rates of first polar body (PB) extrusion than the other groups. Oocytes with a low level of ATP (oocytes with a pale ooplasm without dark clusters) and oocytes with a high level of ATP (oocytes with a black ooplasm) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 18 publications
3
67
1
Order By: Relevance
“…Oocytes were denuded from cumulus cells by vortexing and stained with 1% 16 aceto-orcein as described elsewhere [21]. Nuclear statuses were classified as germinal 17 …”
Section: Evaluation Of Oocyte Nuclear Status 14 15mentioning
confidence: 99%
“…Oocytes were denuded from cumulus cells by vortexing and stained with 1% 16 aceto-orcein as described elsewhere [21]. Nuclear statuses were classified as germinal 17 …”
Section: Evaluation Of Oocyte Nuclear Status 14 15mentioning
confidence: 99%
“…They were then fixed with a mixture of ethanol: acetic acid (3:1), stained with 1% aceto-orcein solution, and nuclear status and the presence of pronuclei were evaluated using a phase-contrast microscope, as described previously [22,23]. Briefly, the presence of two pronuclei was regarded as normal fertilization, whereas three or more pronuclei and/or enlarged sperm heads within an oocyte was judged as polyspermy.…”
Section: Evaluation Of Nuclear Maturation and Fertilization By Whole-mentioning
confidence: 99%
“…In order to determine the effect of these superovulation treatments on oocyte quality, ATP amount in recovered oocytes was determined. It has been described previously that mitochondrial dysfunction and ATP content may be related to developmental competence in oocytes and embryos (Van Blerkom et al, 1995;Thouas et al, 2004;Nagano et al, 2006). Although difference in ATP level was non significant when compared to control group, significant differences in ATP content were found between different superovulatory treatments.…”
Section: Discussionmentioning
confidence: 76%
“…Otherwise, how ATP levels are affected during oocyte maturation seems to be still unclear and seems to be very specie-specific; it has been observed that in vitro maturation and maturation conditions may impact on mitochondrial activity in rabbits , mouse (Combelles y Albertini, 2003), cows Nagano et al, 2006), gilts (Brevini et al, 2005) or cats (Freistedt et al, 2001). …”
Section: Discussionmentioning
confidence: 99%